A British perspective on the critical sociology of religion: A response to Mary Jo Neitz. (August 2015) - Bruce, Steve
In a recent issue of Critical Research on Religion, Mary Jo Neitz presents a four-cell Locations Matrix created by the two dimensions of the status of the religion studied, as dominant and marginal, and position of the researchers vis-à-vis that religion, as insiders or outsiders. Her subsequent arguments about the influence of researcher standpoint perhaps work in the US setting where religion remains popular. This paper points out difficulties in applying the Matrix in the UK setting where religion is unpopular and uses the patently disinterested nature of much of the research conducted by professional sociologists of religion to retrieve the possibility of objective and value-neutral research.